Al2O3 Nanosheets Rich in Pentacoordinate Al3+ Ions Stabilize Pt‐Sn Clusters for Propane Dehydrogenation. (2nd September 2015) - Shi, Lei; Deng, Gao‐Ming; Li, Wen‐Cui; Miao, Shu; Wang, Qing‐Nan; Zhang, Wei‐Ping; Lu, An‐Hui
Abstract: In heterogeneous catalysis, supports play a crucial role in modulating the geometric and electronic structure of the active metal phase for optimizing the catalytic performance. A γ‐Al2 O3 nanosheet that contains 27 % pentacoordinate Al 3+ sites can nicely disperse and stabilize raft‐like Pt‐Sn clusters as a result of strong interactions between metal and support. Consequently, there are strong electronic interactions between the Pt and Sn atoms, resulting in an increase in the electron density of the Pt sites. When used in the propane dehydrogenation reaction, this catalyst displayed an excellent specific activity for propylene formation with >99 % selectivity, and superior anti‐coking and anti‐sintering properties. Its exceptional ability to maintain the high activity and stability at ultrahigh space velocities further showed that the sheet construction of the catalyst facilitated the kinetic transfer process. Abstract : Stabil und selektiv : γ‐Al2 O3 ‐Nanoschichten mit einem hohen Anteil an fünffach koordinierten Al 3+ ‐Ionen können Pt‐Sn‐Cluster exzellent dispergieren und stabilisieren, einhergehend mit einer erhöhten Elektronendichte der Pt‐Zentren. Der Katalysator bewirkt die Umsetzung von Propan zu Propylen mit einer Selektivität von >99 % bei minimaler Verkokung und Sinterung.